2016
DOI: 10.3174/ajnr.a4888
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysfunction in Leukoaraiosis

Abstract: BACKGROUND AND PURPOSE:The pathogenesis of leukoaraiosis has long been debated. This work addresses a less well-studied mechanism, cerebrovascular reactivity, which could play a leading role in the pathogenesis of this disease. Our aim was to evaluate blood flow dysregulation and its relation to leukoaraiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 53 publications
3
40
1
Order By: Relevance
“…(14) Lower CVR, FA, CBF and increased T2 and MD were observed in WMH compared with contralateral normal white matter. (16)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14) Lower CVR, FA, CBF and increased T2 and MD were observed in WMH compared with contralateral normal white matter. (16)…”
Section: Discussionmentioning
confidence: 99%
“…(9,10) Magnetic resonance imaging (MRI) techniques measure CVR in all brain tissues, including the subcortical areas commonly affected by SVD. (11) So far, MRI-based CVR has been assessed in relatively few small studies in SVD, but used different CVR challenges,(12-16) and did not account for clinically-relevant variables (e.g. age, blood pressure [BP], gender) that could confound CVR associations with SVD features.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models demonstrated cerebrovascular dysfunction appeared months ahead of the rst histological evidence of white matter injury, including oligodendrocyte loss and glial activation [35,36]. Previous clinical studies followed up moderate-severe WMH patients for one year and found in comparison with contralateral normal appearing white matter (NAWM) that did not progress, NAWM that progressed to WMH had signi cantly decreased CVR value [30,31]. This result suggested that impaired dynamic cerebrovascular response to hypercapnia precedes the occurrence of WMH and may result in the development of WMH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rs-fMRI has been applied to explore CVR in cerebral large vessel diseases including carotid artery stenosis carotid or occlusion, Moyamoya disease [24,[27][28][29]. Furthermore, emerging studies used BOLD signal technology to evaluate CVR in WMH individuals and found that impaired CVR was associated with WMH [20,30,31]. However, all these studies didn't further explore whether impaired CVR can leads to cognitive decline through WMH.…”
Section: Introductionmentioning
confidence: 99%
“…The observed sparing of cortical U-fibres, which are supplied by shorter arteries, is consistent with such a mechanism. Several cerebral blood flow (CBF) and perfusion studies employing a variety of techniques have shown that resting CBF within WMHs is lower than that in normal-appearing WM in elderly subjects [75,76]. A recent meta-analysis of 28 cross-sectional CBF studies in 1161 elderly individuals showed that CBF was globally reduced in subjects with more WMHs [77].…”
Section: Chronic Cerebral Hypoperfusionmentioning
confidence: 99%